Caracterização dos registros eletrocorticográficos, eletromiográficos e eletrocardiográficos após uso de cafeína em ratos Wistar - CABRAL, Diego Arthur Castro (2023)
Objective: To describe electrocorticographic, electromyographic and electrocardiographic profiles to report the electrophysiological effects of caffeine in Wistar rats. Methods: Male adult Wistar rats weighing 230g to 250g were used. Rats were allocated to one of two groups, as follows: Group 1, Control, intraperitoneal injection of 0.9% saline solution (n=27); and Group 2, treated with intraperitoneal injection of caffeine (50mg/kg; n=27). The rats were submitted to electrocorticographic, electromyographic and electrocardiographic assessment. Results: Brain oscillations (delta, theta, alpha, beta and gamma) in the frequency range up to 40Hz varied after caffeine administration to rats. Powers in delta and theta oscillations ranges were preponderant. The contractile force of the skeletal striated and cardiac muscles increased. Electrocardiogram analysis revealed shorter RR, QRS and QT intervals under the effect of caffeine. Conclusion: In the central nervous system, there was an increase in the delta, theta and alpha amplitude spectrum, which are related to memory encoding and enhanced learning. With regard to skeletal muscle, increased contraction of the gastrocnemius muscle was demonstrated, a clear indication of how caffeine can be used to enhance performance of some physical activities. Electrocardiographic changes observed after caffeine administration are primarily related to increased heart rate and energy consumption.